2008
DOI: 10.1523/jneurosci.1910-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Very Slow EEG Fluctuations Predict the Dynamics of Stimulus Detection and Oscillation Amplitudes in Humans

Abstract: Our ability to perceive weak signals is correlated among consecutive trials and fluctuates slowly over time. Although this "streaking effect" has been known for decades, the underlying neural network phenomena have remained largely unidentified. We examined the dynamics of human behavioral performance and its correlation with infraslow (0.01-0.1 Hz) fluctuations in ongoing brain activity. Full-band electroencephalography revealed prominent infraslow fluctuations during the execution of a somatosensory detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
433
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(476 citation statements)
references
References 31 publications
43
433
0
Order By: Relevance
“…Our findings complement recent findings showing that accurate phase encoding of temporal event structure affords predictability (Schroeder and Lakatos, 2009;Stefanics et al, 2010) and enhances task performance (Busch et al, 2009;Monto et al, 2008;Neuling et al, 2012;Romei et al, 2012;Varela et al, 1981). Our results further suggest that mechanisms analogous to phase precession in the hippocampus may be used in cortex for the encoding of event timing.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings complement recent findings showing that accurate phase encoding of temporal event structure affords predictability (Schroeder and Lakatos, 2009;Stefanics et al, 2010) and enhances task performance (Busch et al, 2009;Monto et al, 2008;Neuling et al, 2012;Romei et al, 2012;Varela et al, 1981). Our results further suggest that mechanisms analogous to phase precession in the hippocampus may be used in cortex for the encoding of event timing.…”
Section: Resultssupporting
confidence: 91%
“…It is well known that distinct phases of low-frequency neural oscillations are associated with periods of high and low neural excitability (Buzsáki, 2010;Lakatos et al, 2008). These fluctuations have been shown to impose temporal constraints on the "what" of perception by modulating the perceptual detection threshold of various stimuli (Busch et al, 2009;Fiebelkorn et al, 2013;Henry and Obleser, 2012;Monto et al, 2008;Neuling et al, 2012). They have also been proposed to serve parsing and informational chunking of sensory information over time (VanRullen and Koch, 2003) notably for complex temporal structures such as speech (Giraud and Poeppel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we were not limited to only sensorimotor ROIs in our approach. The interconnected nature of the activity structure of infraslow and slow activity is consistent with a cross-frequency phase-amplitude coupling relationship that has previously been indicated for infraslow fluctuations in EEG and MEG recordings in human subjects [13][14][15]60 .…”
Section: Discussionsupporting
confidence: 87%
“…In the developing brain, electrophysiological infraslow activity in the form of neuronal activity transients or bursting activity has been linked with the development of neuronal networks 11,12 , whereas in the adult brain, infraslow activity has been demonstrated to synchronize with higher-frequency brain activity 13,14 and to correlate to variability in behavioural performance 15,16 . Renewed focus on the nature of spontaneous resting-state infraslow activity has been precipitated due to an immense proliferation of functional neuroimaging studies that have revealed much about the brain's functional organization and have identified what has been described as the brain's Default Mode Network (DMN) 17 , a network of brain structures that are coherently, highly active at rest and reduced during active task performance 18 .…”
mentioning
confidence: 99%
“…Moreover, VLFOs are thought to contribute to inter-trial variability in evoked responses and behaviour Monto et al, 2008;Demanuele et al, 2010).…”
Section: Introductionmentioning
confidence: 99%